The principle of natural law show Complete Scientific Modeling" with its internet could inclusive of all human faith, knowledge and experience. The world peace come from all the personality together blooming and complement each other - sandstrom, Yansha Yu (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper, based on Humankinds interdisciplinary and complete theory of mutual cognition publishing by china Xian Zhuang Publisher and The principle of cosmic life being multi-dimensional and simultaneously evolving Published by Frontier Science 2014 Vol. Issue 2 Chinaï¼ Abbreviation The principle of natural law. For example: The complete universe is a solid ball. All humans cognitions and certifications are this solid ball itself and each of its levels, angles, positions, interfaces... Presence Ways and Presence Relationships. When all humans cognitions and certifications, departure from their respective standpoint and attributes, reaches to each other's standpoint and attributes. That will become same one song played in different tones (as each other or each own). Otherwise people will each stick to their own limited area, disagree and no-inclusive other side. Basis on the above, The principle of natural law don't against any of human experience and knowledge. It clarifies all human cognitions and certifications where are they located at the system of universe, what people has been find out or not grasp yet. How could from people knowing arrival to their unknowing, and final build all human consensus. For help different disciplines reach consensus, The principle of natural law will combine with each disciplines examples, and follow three big basic theorem steps to show that same one song how could play with different tones.